(untitled) (Journal of Rashid Latif Medical College, 2024)
Objective: Global health concerns about gestational diabetes mellitus (GDM) are growing. For prompt prevention and management, early and precise awareness of GDM is essential, particularly for young individuals. The purpose of this study is to determine the factors impacting the degree of GDM knowledge among students at a private medical university. Methodology: Students at medical universities participated in a cross-sectional study utilizing a validated self-administered questionnaire. The survey evaluated students' knowledge of GDM (classified as poor, fair, or good) and awareness of the condition (i.e., if they had ever heard of it). Factors linked to GDM understanding were found using ordinal logistic regression. Results: 735 students in all, with an average age of 21.0 years, took part in the study. 72.8% of participants said they have heard of GDM. Interestingly, 20.3% of female students and 52.9% of male students were unaware of GDM. Male students' greater GDM knowledge was linked to their age (p = 0.019) and postgraduate status (p = 0.026). Twenty-four percent had weak knowledge, fifty-eight percent had fair knowledge, and seventeen percent had strong knowledge. Out of 12, the average GDM knowledge score was 6.3 ± 2.4. Being married (aOR = 1.82, 95% CI 1.10–3.03) and knowing someone with GDM (aOR = 1.78, 95% CI 1.23–2.60) were factors that were independently linked to greater knowledge. Friends and relatives served as the main information sources. Conclusion: This study shows that medical university students, particularly male students, have a substantial knowledge gap about GDM. Better knowledge is linked to factors like marital status and firsthand experience with GDM. These results highlight the necessity of focused educational initiatives on GDM awareness in order to raise awareness among college students and the general public in Pakistan. Keywords: Gestational Diabetes Mellitus, Students, GDM, Knowledge.